Sure! Let's go through the operations clearly and concisely.
a. Addition
Let's add \(3.2 \times 10^4\) and \(2.56 \times 10^{-2}\).
-
Before adding, we need to express both numbers with the same exponent. We can convert \(3.2 \times 10^4\) into an equivalent form with \(10^{-2}\):
- \(3.2 \times 10^4 = 3.2 \times 10^4 \times \frac{10^6}{10^6} = 3.2 \times 10^6 \times 10^{-2} = 3.2 \times 1000000 \times 0.01 = 3200000 \times 0.01 = 32000\)
-
Therefore, we can write:
- \(3.2 \times 10^4 = 32000 \times 10^{-2}\)
- \(2.56 \times 10^{-2}\) remains the same.
-
Now we can add: \[ 3.2 \times 10^4 + 2.56 \times 10^{-2} = 32000 \times 10^{-2} + 2.56 \times 10^{-2} = (32000 + 2.56) \times 10^{-2} = 32002.56 \times 10^{-2} \]
-
Converting back to scientific notation:
- \(32.00256 \times 10^2\) (which is \(3.200256 \times 10^4\)).
Result of Addition:
\[ 3.200256 \times 10^4 \]
b. Subtraction
Let's subtract \(1.95 \times 10^6\) from \(4.82 \times 10^{12}\).
-
To perform the subtraction, it's best to express both numbers in the same base. We can convert \(4.82 \times 10^{12}\) into an equivalent form with \(10^{6}\):
- \(4.82 \times 10^{12} = 4.82 \times 10^{12 - 6} \times 10^{6} = 4.82 \times 10^6 \times 10^6 = 4.82 \times 1000000\)
-
So, we can write:
- \(4.82 \times 10^{12} = 4.82 \times 10^{6} \times 1000000 = 4820000000 \)
-
Now we can subtract: \[ 4.82 \times 10^{12} - 1.95 \times 10^{6} = 4820000000 - 1.95 \times 10^6 = 4820000000 - 1950000 = 4818050000 \]
-
Converting to scientific notation:
- \(4.818050000 \times 10^9\) (which is \(4.81 \times 10^9\) rounded).
Result of Subtraction:
\[ 4.81 \times 10^9 \]
In summary:
- Addition Result: \(3.200256 \times 10^4\)
- Subtraction Result: \(4.81 \times 10^9\)